Generation Y Purchase Intention of Personal Care Products: The Influence of Attitude, Subjective Norms and Perceived Behavioural Control / Noor’ain Mohamad Yunus, Rohana Mat Som, Afiza Abdul Majid, Ungku Munirah Ungku Abdul Aziz, Mohd Khalid Mohd Abas - Mohamad Yunus, Noor’ain; Mat Som, Rohana; Abdul Majid, Afiza; Ungku Abdul Aziz, Ungku Munirah; Mohd Abas, Mohd Khalid (Faculty of Business and Management ; UiTM Press, 2018)
Rising cost of living in Malaysia has negatively affected the demand for personal care products as consumers prefer to switch to cheaper alternatives. This has resulted in an increase in the number of registered and unregistered personal care products in the market. This situation has an impact on Malaysian consumption as some of the products contain hazardous and poisonous ingredients which may cause adverse effects on personal health. However, customers still consume the products although they are aware and conscious of the danger and the side effects of these products for self-satisfaction. Thus, using the Theory of Planned Behaviour (TPB), this study aims to shed further light on the factors that influence consumer decision making in the purchase of personal care products among Generation Y. The study was conducted using primary approach with the use of validated questionnaire from 390 university students. The findings revealed that subjective norm and perceived behavioural control influence consumer decision making. Findings provide evidence for businesses and policy makers to better understand the factors that influence consumer decision making. Further implications allow authorized body to identify the target group and conduct programs to educate consumers to engage in good judgement before making decisions to ensure healthy consumption choices aligned with the National Strategic Plan on promoting optimal healthy lifestyles.